The Lactic Acid Bacteria in Fermented Durian (D. Zibethinus ) - Hasanuddin Hasanuddin (AGRITROPICA : Journal of Agricultural Sciences, 2021)
Lactic acid (C2H5COOH) is the organic acid that  can serve as a food preservation. The group of bacteria which can produce lactic acid in their fermentation process known as Lactic Acid Bacteria (LAB). A fundamental biochemical change of fermentation is that an acidic environment is created. Many harmful organisms cannot exist in acidic solution so the fermentation productions are save to eat. Fermented Durian is the fermented food prepared from spontaneous fermentation of durian (Durio zibethinus) with or without salt by wild bacteria. The research was conducted to isolate and identify lactic acid bacteria in tempoyak. The data in this study were laboratory analysis. Samples were collected weekly in a month analyzed microbiologically from traditionl markets in Bengkulu. There were four species of lactic acid bacteria involved in fermented durian namely Leuconostoc mesentroides, Pediococcus acidilactici, Lactobacillus plantarum, and Lactobacillus curvatus.